Free Listening - Kyle A. Hanners; Cristopher J. Tietsort (Journal of the Scholarship of Teaching and Learning, 2021)
Given the widespread ideological polarization of the current times, cultivating ways to empathize across difference has never been more important. In this essay, we outline Free Listening (FL), a pedagogical practice that helps people grow their capacity to empathetically engage others across difference by engaging in structured sessions of active empathetic listening. Our prior work demonstrates that the structured practice of FL has both affective and practical implications for how students engage with others; students leave the practice with a greater sense of awareness, appreciation for other cultures, and ability to listen across cultural and ideological boundaries. We believe FL has great promise within the teaching-and-learning process in relation to civic and community engagement, service learning, and relational praxis. In this essay, we outline the practice of FL and review literature that helps elucidate what this practice is and does. Some key themes are discussed that reveal the valuable contributions of this practice as they have emerged from our students’ and our own experience with/in FL. Finally, we trace the pedagogical implications of FL as they connect to theories of dialogue and dialogic praxis. Overall, we argue that FL should be a regular practice for pedagogues across the social sciences in order to cultivate in students the relational and empathetic skills that are needed to advance the project of depolarization—a project in which other-centeredness should be a defining feature.